2016
DOI: 10.1007/s00167-016-4202-2
|View full text |Cite
|
Sign up to set email alerts
|

Infections following arthroscopic rotator cuff repair: incidence, risk factors, and prophylaxis

Abstract: Retrospective comparative study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
6
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 29 publications
8
56
6
4
Order By: Relevance
“…Deep infections of the shoulder after arthroscopic RCR are uncommon. The results of the present study indicate an overall deep infection rate of 0.44% that appears to be lower than the rate of 0.85% reported by Pauzenberger et al 5 . This difference in rate of infection can possibly be attributed to the difference be- tween the number of patients included in the present study and the study from Pauzenberger et al 5 1,6,7,12,13 .…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Deep infections of the shoulder after arthroscopic RCR are uncommon. The results of the present study indicate an overall deep infection rate of 0.44% that appears to be lower than the rate of 0.85% reported by Pauzenberger et al 5 . This difference in rate of infection can possibly be attributed to the difference be- tween the number of patients included in the present study and the study from Pauzenberger et al 5 1,6,7,12,13 .…”
Section: Discussioncontrasting
confidence: 81%
“…Microbiological evaluation revealed positive culture results in all except for one patient, who was started on oral antibiotics by his family physician before he was seen by the operating surgeon. Seven patients had growth of single microorganisms including Staphylococcus aureus (5), Propionibacterium acnes (1), and Phaeoacremonium parasiticum (1). Culture results from each of the remaining two patients showed growth of two microorganisms: Propionibacterium acnes with Staphylococcus saccharolyticus, and Staphylococcus epidermidis with Staphylococcus saccharolyticus.…”
Section: Resultsmentioning
confidence: 99%
“…They reported, similar to other studies, that constitutional symptoms such as fever or chills were less commonly seen 6 8 9 13. Pauzenberger et al 14 noted the only symptom consistently present in all patients with an infection was diffuse shoulder pain; however, this complaint is commonly found in the early weeks following any shoulder surgery. They concluded that in patients with shoulder pain after an uneventful initial rehabilitation phase, infectious complications should be considered, even in the absence of clinical signs of infection.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of RCRs are performed using braided, non-absorbable suture, which creates a favourable environment for bacteria given the increased surface area compared with monofilament suture. Pauzenberger et al 14 performed a retrospective study of 3294 arthroscopic RCRs, including 28 infections during a 10-year period. Surgical treatment in their group included open I & D for 26 patients, with only two patients undergoing arthroscopic I & D, and removal of anchors and suture material in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of rotator cuff tears has become one of the most common orthopaedic sports procedures [1,2]. While this operation has a low morbidity, it is not without risk for complications such as chondrolysis, athrofibrosis, nerve damage, and infection [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%